EFFECT OF CYTOKININS ON in vitro MULTIPLICATION OF RHUBARB (Rheum rhaponticum L.) ‘KARPOW LIPSKIEGO’ SHOOTS AND ex vitro ACCLIMATIZATION AND GROWTH - Danuta Kozak; Andrzej Sałata (Acta Scientiarum Polonorum: Hortorum Cultus, 2011)
The influence of four cytokinins: BA (4.4, 11.1, 22.2 μmol·dm-3), kinetin (4.7, 11.6, 23.3 μmol·dm-3), 2iP (4.9, 12.3, 24.6 μmol·dm-3), TDZ (4.5, 11.4, 22.7 μmol·dm-3) on shoot multiplication of Rheum rhaponticum ‘Karpow Lipskiego’ on Murashige and Skoog (MS) medium was studied. The shoots used in the experiment were obtained from aseptically grown shoot clusters. Rooted shoots (except treatment with TDZ) after acclimatization were transplanted to pots into a peat substrate where they were grown for 4 weeks. Plants were then cultivated in the field for 8 months. During in vitro studies the cytokinins promoted the development of leaves as well as the formation of new shoots. The highest average number of axillary shoots was found on the medium with BA 11.1–22.2 μmol·dm-3. The use of kinetin (4.7–11.6 μmol·dm-3) or 2iP 12.3 μmol·dm-3 stimulated strong growth of shoots expressed in their length and size of the leaf blade. All TDZ concentrations caused a significant inhibition of shoot elongation. BA and TDZ had a harmful effect on the rooting of multishoots. On the control medium (hormone-free) and on the media containing kinetin or 2iP, 100% of shoots produced roots. After a period of 8 months, following overwintering and start of vegetation growth, the plant survival rate was 80–100%. It was found that 2iP 12.3 μmol·dm-3 had the highest after effect on plant growth. The plants derived from this medium had uniform and compact growth and they developed more leaves in the rosette with significantly larger laminae as well as longer and thicker petioles, than plants obtained from others used media.